Significance of Carbon Farming for Improved Household Incomes in Baringo County, Kenya - Kiprop John; Sumukwo Joel; Odwori Paul (African Journal of Education,Science and Technology (AJEST), 2025)
Smallholder agriculture has been a mainstay of livelihoods in Baringo County for decades, but due to climate change effects, it’s dependency is extremely challenged. Using survey data of 380 households collected using stratified random sampling, factors influencing climate information for improved carbon farming among smallholder farmers were analysed. Eldama Ravine and Baringo central sub-counties were chosen for the study because of their ecological diversity, agribusiness significance, and vulnerability to climate change. Results revealed that the best media to use in sharing climate information in Baringo county was television (78%) while the least was newspapers (0.3%), probably because of affordability of newspapers. Gender influenced awareness and access to climate information since that male (64%) had higher awareness and access than female (55%). it was also noted that Most (89%) of the respondents agreed and strongly agreed that accessibility of smallholder farmer to agricultural extension services played important role in accessing climate information. ANOVA and Multiple regression (R2, 0.54) results displayed age(B = -0.44,p = 0.104), gender(B = 0.014, p = 0.048), education level(B = 0.021, p = 0.058), and household income(B = 0.062, p = 0.007) were significant in influencing climate information. This study concludes agricultural extension information to be important in accessing climate information and the need of empowering women in farm decision-making. It is recommended that gender-sensitive approaches be incorporated into agricultural extension services to empower women in decision-making and bridge the gender gap in climate information access.